Financial Incentive Does Not Affect P300 in the Complex Trial Protocol (CTP) Version of the Concealed Information Test (CIT) in Malingering Detection. II. Uninstructed Subjects - Rosenfeld, J. Peter; Davydova, Elena; Labkovsky, Elena; Ward, Anne (Frontiers in Psychiatry, 2019)
Well-known research showed that the skin conductance response (SCR) of the Autonomic Nervous System (ANS) in the Concealed Information Test (CIT) is usually augmented in participants who are financially and motivationally incentivized to beat the CIT. This is not what happens with Reaction Time (RT)-based CITs, P300 CITs based on the 3-stimulus protocol, nor on the P300-based complex trial protocol for detection of malingering (however these tests differ from forensic CITs). The present report follows up the Rosenfeld et al. (1, 2) study of motivated malingerers instructed how to beat the test, with uninstructed motivated (paid and unpaid) and unmotivated (“simple malingering”) subjects, using episodic and semantic memory probes. The Test of Memory Malingering (TOMM) validated behavioral differences among groups. The “CIT effect” (probe-minus-irrelevant P300 differences) did not differ among incentive groups, although as previously, semantic memory-evoked P300s exceeded episodic memory evoked P300s. An effect of specific test-beating instructions was found to enhance the CIT effect for semantic information.